The challenge of managing the Columbia River Basin for energy and fish. (February 2015) - Leonard, N. J.; Fritsch, M. A.; Ruff, J. D.; Fazio, J. F.; Harrison, J.; Grover, T.
Abstract The Columbia River Basin (Basin) is located in the Pacific Northwest, United States. The 370 hydroelectric dams in the Basin provide the Pacific Northwest with many services including hydropower generation, flood control, agricultural irrigation and navigation. The basin also provides habitat for a variety of anadromous and resident fishes and wildlife species. Balancing the energy demands with the needs of fish and wildlife is a daunting task. Through the implementation of the Pacific Northwest Electric Power Planning and Conservation Act (Power Act), the Council, in collaboration with state, federal, tribal and non‐governmental partners, attempts to address the needs of fish and wildlife with that of hydropower generation. The implementation has become increasingly challenging as the Basin's ecosystem continues to be impacted by societal demands and the resulting environmental impacts. The focus of this paper is the ongoing challenge of meeting the demands on hydropower generation and of the basin's fish species.